Fabrication Of Dye-Sensitized Solar Cells Using Aqueous And Ethanolic Extracts Of Ixora Macrothyrsa Flowers (Applied Biological Research, 2022)
Dye-sensitized solar cells (DSSCs) are promising types of photovoltaic cells  which have the capability to generate electrical energy at low fabrication cost in comparison to the silicon crystalline solar cells. Titanium dioxide  (TiO2) nanoparticles were synthesized by solvothermal method. DSSCs  using Ixora macrothyrsa flowers as dye-sensitizer were fabricated using  l as solvents. The structural and surface properties of  TiO2 nanoparticles were characterized using X-ray diffraction and Field  Emission Scanning Electron Microscopy. The synthesized TiO2 material  had tetragonal crystal structure which was highly stable and crystalline.  The extracted natural dyes were characterized by UV-visible absorption  pectroscopy and Fourier transform infrared (FTIR). The bandgap energy  of TiO2 photoanode was studied by using UV-visible spectra and the  y using FTIR spectra. The photo-electrochemical  parameters and efficiency of DSSC were measured using-measurement system. The result of J-V characteristics showed that the  efficiency of DSSC’s based on TiO2 nanoparticles extracted from Ixora flowers using ethanol solvent was better than water solvent.
Keywords: FTO; photovoltaics; Ixora; solvothermal; TiO2